2012
DOI: 10.1016/j.jsps.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive buccal patches based on interpolymer complexes of chitosan–pectin for delivery of carvedilol

Abstract: The study was designed to develop bioadhesive patches of carvedilol hydrochloride using chitosan (CH) and pectin (PE) interpolymer complexes and to systematically evaluate their in vitro and in vivo performances. Mucoadhesive buccal patches of carvedilol were prepared using solvent casting method. The physicochemical interaction between CH and PE was investigated by FTIR and DSC studies. The patches were evaluated for their physical characteristics like mass variation, content uniformity, folding endurance, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…Variety of dosage forms like tablets (Boyapally et al, 2010, Kanjanabat & Pongjanyakul, 2011, discs (Yehia et al, 2008;Jaipal et al, 2013), patches (Abu-Huwaij et al, 2011;Kaur & Kaur, 2012;Govindasamy et al, 2013) and gels (Das et al, 2012;Bueno et al, 2013) have been reported in the literature for buccal delivery of drugs. Buccal discs are flat, thin solid unit non-flexible compacts; and are similar to buccal tablets.…”
Section: Introductionmentioning
confidence: 99%
“…Variety of dosage forms like tablets (Boyapally et al, 2010, Kanjanabat & Pongjanyakul, 2011, discs (Yehia et al, 2008;Jaipal et al, 2013), patches (Abu-Huwaij et al, 2011;Kaur & Kaur, 2012;Govindasamy et al, 2013) and gels (Das et al, 2012;Bueno et al, 2013) have been reported in the literature for buccal delivery of drugs. Buccal discs are flat, thin solid unit non-flexible compacts; and are similar to buccal tablets.…”
Section: Introductionmentioning
confidence: 99%
“…3a). This figure also shows that the maximum swelling percentage (182.7%±8.1) of PC tablets was achieved after 7 h due to gel formation, uncoiling of the structure of PC molecules, and the formation of hydrogen bonds with water molecules (59). The swelling of PC tablets was significantly (p < 0.05) lower than SCMC or CP.…”
Section: Degree Of Tablets Swellingmentioning
confidence: 69%
“…Swelling study [14,15] Buccal patches were weighed individually (W 1 ) and placed separately in 2% agar gel plates with the core facing the gel surface and incubated at 37 ± 1°C. At regular intervals (30, 60…300 min) the patches were removed from Petri dishes and excess water removed The patches were tested for the content uniformity.…”
Section: Thicknessmentioning
confidence: 99%
“…Just before the experiment, it was thawed at room temperature and checked for any damage. [15,22,23] The in vitro drug release studies were conducted by using Franz diffusion cells and were performed in phosphate buffer (pH 7.4). The volume of buffer in the receiver compartment was 18 ml.…”
Section: In Vitro Permeation Study A) Tissue Preparationmentioning
confidence: 99%